Digital TV: the aparattus and the representation of real on image edition in news casting TV Digital: o aparelho e a representação do real na edição de imagens no telejornalismo - Fernanda Aiex Boni (Discursos Fotográficos, 2011)
This study investigates some changes on image edition due to the transfer of Analogic to Digital Television in Brazil. Beginning with Vilém Flusser’s Media Theory and its concept of “apparatus”, it develops a theoretical analysis of the new relationship between journalists and digital editing instruments, taking into account the concept of hyperreality proposed by Jean Baudrillard. Retrieving the philosophical discourse of “real” throughout History and also the positivist concepts, base of the journalistic activity, it discusses how digital image manipulation and the construction of graphic universes meddle with the new representation of real presented by television news casting. From interviews with Rede Globo editors in São Paulo, Rio de Janeiro and Curitiba (cities where digital television has already been implemented), it analyses how this new technology can hinder the main commitment of journalism, which is reporting facts as faithfully as possible. The discussion proposes an engagement of professionals and society regarding digital images in the search of greater critical conscience towards digital images in news casting, with an ethic view of the use of manipulation resources and scene construction on news editing. Este trabalho investiga algumas mudanças na edição de imagens com a passagem da TV Analógica para a Digital no Brasil. A partir da teoria da mídia de Vilém Flusser e seu conceito de “aparelho” desenvolve-se uma análise teórica da nova relação entre os jornalistas e os equipamentos digitais de edição, levando-se em conta o conceito de hiper-realidade, proposto por Jean Baudrillard. Retomando o percurso filosófico do real ao longo da história e ainda os conceitos positivistas, que embasam a atividade jornalística, discute-se de que maneira a manipulação das imagens digitais e a construção deuniversos gráficos interferem na nova representação do real apresentada pelo telejornalismo. Com base em entrevistas com editores da Rede Globo em São Paulo, Rio de Janeiro e Curitiba (cidades onde a TV Digital já foi implantada), analisa-se a maneira como a nova tecnologia pode interferir no compromisso primeiro do jornalismo, que é o de relatar os fatos da maneira mais fiel possível. A discussão propõe um engajamento dos profissionais e da sociedade em busca de uma maior consciência crítica em relação às imagens digitais no jornalismo, com uma visão ética do uso dos recursos de manipulação e construção de cenas na edição das notícias.